Tren Kepatuhan Pelaku Usaha Bidang Kosmetik di Indonesia - Sri Astuti; Tina Wikara; Sri Nurhayati; Evi Ratna Sari; Rotua Uli Carolina; Galuh Zhafirah Rahmita (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Compliance of business actors with regulations and standards such as the Good Manufacturing Practice (GMP) and regulations on the distribution, advertising and labelling of cosmetics is a crucial aspect in ensuring the safety and quality of cosmetic products to protect public health. This study aimed to assess the level of compliance of cosmetics business actors with regulations and standards in Indonesia. This quantitative study analyzed secondary data from the Indonesian FDA (BPOM)’s risk-based supervision of production and distribution facilities, advertising, and labelling across 34 provinces from 2019–2023. Each year, 4270–7,054 facilities were inspected and classified as compliant or non-compliant, and compliance proportions were calculated. The results were weighted using the Analytical Hierarchy Process (AHP) to produce a compliance index categorized into four levels: excellent (90.01–100), good (66.67–90), fair (33.34–66.66), and poor (0–33.33). The results of the analysis showed that the compliance index of cosmetics businesses for five years ranged from 71.62 to 83.79 and was classified as good: 82.79 (2019), 80.96 (2020), 75.41 (2021), 71.62 (2022), and 83.79 (2023). The index trend showed a fluctuating pattern from year to year, with the highest value recorded in 2023.